MICROSTRUCTURE OF THE MID-INTESTINE OF CERTAIN CARP FISH (CIPRINIDAE) IN THE WESTERN PART OF THE MIDDLE CASPIAN SEA - N. I. Rabazanov; Z. M. Kurbanov; R. M. Barkhalov; M. S. Kurbanov; M. A. Mammaev; K. M. Akhmedkhanov; A. A. Butaeva; E. N. Lobachev (Юг России: экология, развитие, 2017)
Aim. The aim of the study was an attempt to expand on the findings about the structure of the anterior part of the mid-intestine of three species of carp fish: Rutelus frisii kutum (Kamenski), Abramis brama orientalis and Ciprinus caprio (Linne) in connection with the feeding habits in the changed conditions of the western coast of the Middle Caspian sea. Studies of the digestive tract can extend the idea of the specifics of the mid-intestine structure due to the feeding of fish in certain environmental conditions of habitat.Methods. Investigations of the digestive tract were carried out, guided by the "Methodological manual" by I.V. Verigina.Findings and discussion. It is shown that in the anatomical and histological structure of the middle intestine was affected by the feeding habits of these types of fish; feeding upon small and soft invertebrates leads to a relatively simple structure of the intestinal wall: mucous layer covers a small part of the total thickness of the wall; there are no collagen structures that perform the function of the mechanical frame and capsules around blood vessels.Conclusion. Simplification of the digestive system emphasizes adaptive capacity appearing in periodic fluctuation of sea water level. The absence of food of a bigger size in the diet of fish results in a relatively simple anatomical and histological structure of the mid-intestine wall. None of the species under study has a differentiated stomach; instead its role is taken by an expanded portion of the fore intestine, similar is the microstructure of the middle part of the intestines of all three species.